2003
DOI: 10.1002/jcb.10510
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of albumin expression in bone tissues with healing rat fractures

Abstract: The characterization of 66 kDa protein molecule, a major protein component which is produced from femoral-diaphyseal tissues with fracture healing (Igarashi and Yamaguchi [2002] Int. J. Mol. Med. 9:503-508), was investigated. Weaning rats were killed at 7 and 14 days after femoral fracture. When the femoral-diaphyseal tissues with fracture healing were cultured for 48 h in a serum-free medium, many proteins in the bone tissues were released into the medium. Analysis with sodium dodecyl sulfate-polyacrylamide g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…6D). Moreover, "ectopic" albumin expression has been previously described in healing bone (18); skin (19); granulosa cells (20); kidney and pancreas (21); and mammary gland (22). Furthermore, albumin was described to affect The T cells were harvested after 1, 2, or 3 h. Cytoplasmic and nuclear fractions were run on SDS transferred to nitrocellulose and tested with Pen 9 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…6D). Moreover, "ectopic" albumin expression has been previously described in healing bone (18); skin (19); granulosa cells (20); kidney and pancreas (21); and mammary gland (22). Furthermore, albumin was described to affect The T cells were harvested after 1, 2, or 3 h. Cytoplasmic and nuclear fractions were run on SDS transferred to nitrocellulose and tested with Pen 9 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies by Yamaguchi and colleagues have suggested that albumin is released by osteoblast cells present in fracture healing sites and this excess albumin increases the proliferation state of the surrounding cells. [49][50][51] In one of these studies, Ishida and Yamaguchi showed that supplementing a standard culture medium with varying amounts of BSA led to a significant increase in the number of MC3T3-E1 cells present after 24, 48, and 72 hours of culture in a dose dependent manner. 49 A similar trend was seen in the number of cells present in this study after only 5 total hours of cell culture (2 hours of adhesion and 3 hours of MTT uptake) as shown in Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yamaguchi et al . [18] provided convincing evidence of albumin synthesis in bone tissues cultured in serum-, albumin-free medium. There has been no specific report about the synthesis of albumin in brain either at the mRNA level or at the protein level.…”
Section: Introductionmentioning
confidence: 92%